The role of mediating work-life balance in causal relationships between organizational virtue and organizational citizenship behavior of teachers - hafez sahebyar; Abolfazl Farid (Allameh Tabataba'i University Press, 2019)
This study aimed to investigate the mediating role of work-life balance in causal relationships between organizational virtue and organizational citizenship behavior of teachers and suggest a causal model in relation to it. The study population included all staff of Kaleybar district schools who were selected by cluster sampling method and Cochran's formula, 200 people. The present study is applied in terms of purpose and descriptive-correlational in terms of method. Standard data questionnaires were used to collect data, all of which had good validity and reliability. The research data were analyzed using SPSS and lisrel software in the form of t-tests and structural equation modeling.The results show that the organizational virtue of schools directly has a significant effect on the organizational citizenship behavior of Kaleybar education staff; Also, the hypothetical model test shows that organizational virtue can influence teachers' organizational citizenship behavior by mediating work-life balance. The research findings emphasize the importance of organizational virtue of schools and the organizational citizenship behavior of employees, as well as the work-life balance of teachers.